ANGKA LEMPENG TOTAL BAKTERI IKAN KUNIRAN DAN IKAN TONGKOL ASAP DI PASAR BARU TUBAN - Sriwulan Sriwulan; Isaiah Imam Murtadho; Isaiah Imam Mawardi; Hana Dwi Andayani; Yuni Alina; Nia Nurfitria (Binar – Biology Natural Resources Journal, 2022)
Smoked fish is one of the product based fish in Tuban Regency. Smoked fish is widely sold in traditional markets in Tuban Regency, one of which is Pasar Baru Tuban. Smoked fish production carried out by smoked fish producers in Tuban is mostly done traditionally, so the quality is not guaranteed and less hygienic. One of the important quality parameters is the microbiological parameter based on the total bacterial plate number. The purpose of this study was to determine the total plate number of bacteria in smoked fish in Pasar Baru Tuban. This research is an exploratory descriptive study which was carried out through several stages, namely sampling (tongkol smoked fish and kuniran smoked fish) taken from smoked fish traders in Pasar Baru Tuban, preparation of tools and materials, serial dilution, isolation of bacteria, and counting the total number of bacteria plates. The results obtained in this study are the Total Bacterial Plate Number of smoked kuniran fish is 1.2 X 105 cfu/gram and the Total Bacteria Plate Number of tongkol smoked fish is 1,5 X 105 cfu/gram.. The conclusion of this study is that the total bacterial plate count of smoked fish meet the SNI for smoked fish products.